The Paradoxical Behavior of microRNA-211 in Melanomas and Other Human Cancers - Ray, Animesh; Kunhiraman, Haritha; Perera, Ranjan J. (Frontiers in Oncology, 2021)
Cancer initiation, progression, and metastasis leverage many regulatory agents, such as signaling molecules, transcription factors, and regulatory RNA molecules. Among these, regulatory non-coding RNAs have emerged as molecules that control multiple cancer types and their pathologic properties. The microRNA211 (MIR211) is one such molecule, which affects several cancer types, including melanoma, glioblastoma, lung adenocarcinomas, breast, ovarian, prostate, and colorectal carcinoma. Previous studies suggested that in certain tumors MIR211 acts as a tumor suppressor while in others it behaves as an oncogenic regulator. Here we summarize the known molecular genetic mechanisms that regulate MIR211 gene expression and molecular pathways that are in turn controlled by MIR211 itself. We discuss how cellular and epigenetic contexts modulate the biological effects of MIR211, which exhibit pleiotropic effects. For example, up-regulation of MIR211 expression down-regulates Warburg effect in melanoma tumor cells associated with an inhibition of the growth of human melanoma cells in vitro, and yet these conditions robustly increase tumor growth in xenografted mice. Signaling through the DUSP6-ERK5 pathway is modulated by MIR211 in BRAFV600E driven melanoma tumors, and this function is involved in the resistance of tumor cells to the BRAF inhibitor, Vemurafenib. We discuss several alternate but testable models, involving stochastic cell-to-cell expression heterogeneity due to multiple equilibria involving feedback circuits, intracellular communication, and genetic variation at MIRNA target sties, to reconcile the paradoxical effects of MIR211 on tumorigenesis. Understanding the precise role of this MIRNA is crucial to understanding the genetic basis of melanoma as well as the other cancer types where this regulatory molecule has important influences. We hope this review will inspire novel directions in this field.